Driving Profitability: Exploring The Impact of Diversifying Environmentally Friendly Project Credits on Bank Performance (Jurnal Manajemen Bisnis, 2023)
Green finance is a concept that combines financial and environmental aspects, focusing on sustainable and environmentally friendly investments. This research aims to examine the impact of expanding the allocation of green project loans on bank profitability. The study utilizes secondary data obtained from financial reports of banks and other financial institutions, as well as data related to green finance policies and regulations in Indonesia. The hypotheses are tested using the GMM method for data processing, with Stata17 as the main platform. The results indicate that the disbursement of green credit (GC) has a significant negative effect on the bank's Return on Assets (ROA). However, it does not have a significant influence on the Net Interest Margin (NIM). The research provides recommendations to enhance awareness and understanding of green finance through educational campaigns and training. Efforts are also needed to improve access to relevant data and information on green finance, and to strengthen collaboration among the government, financial institutions, and private sector in developing a more inclusive and sustainable green finance ecosystem in Indonesia.